2019
DOI: 10.4266/acc.2018.00339
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implication of Adrenocortical Response during the Course of Critical Illness

Abstract: BackgroundCritical illness-related corticosteroid insufficiency (CIRCI) and adrenocorticotropic hormone (ACTH)-cortisol dissociation are hormonal conditions frequently observed in patients in the intensive care unit (ICU). The aim of this study was to evaluate the association between ACTH-cortisol dissociation and clinical outcomes of critically ill patients. MethodsWe retrospectively reviewed the medical records of 94 ICU patients who underwent two rapid cosyntropin tests during hospital admission and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…As previously reported (23), the CIRCI group had significantly lower cortisol levels than the non-CIRCI group.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As previously reported (23), the CIRCI group had significantly lower cortisol levels than the non-CIRCI group.…”
Section: Discussionsupporting
confidence: 87%
“…de Jong et al (36) found significantly lower hospital stay in patients without CIRCI. On the contrary, most other studies showed an insignificant difference (20,22,23). These contradictory results could be attributable to the characteristics of the cohort.…”
Section: Discussionmentioning
confidence: 78%
“…More than half of our mechanically ventilated patients had CIRCI, and the presence of CIRCI was not associated with increased mortality. Other studies have also shown that the presence of CIRCI does not affect the outcome of critically ill patients [ 20 - 22 ]. Another interesting finding of this study was that that delta salivary cortisol, but not the delta serum cortisol, was significantly higher in survivors than in non-survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Assumed mechanisms involve decreased hepatic inactivation, decreased renal excretion, lower levels of cortisol binding globulin, increased levels of bile acids or direct stimulation of cortisol synthesis, and release by inflammatory cytokines [34]. Also, it has been demonstrated that ACTH/cortisol dissociation has a negative impact on prognosis [33][34][35]. As glucocorticoids suppress AVP secretion, this hypercortisolemic state during critical illness might be a reason for the lower copeptin levels at day 3 in non-survivors.…”
Section: Plos Onementioning
confidence: 99%